16p13.11 deletion variants associated with neuropsychiatric disorders cause morphological and synaptic changes in induced pluripotent stem cell-derived neurons - Buttermore, Elizabeth D.; Anderson, Nickesha C.; Chen, Pin-Fang; Makhortova, Nina R.; Kim, Kristina H.; Wafa, Syed M. A.; Dwyer, Sean; Micozzi, John M.; Winden, Kellen D.; Zhang, Bo; Han, Min-Joon; Kleiman, Robin J.; et al. (Frontiers in Psychiatry, 2022)
16p13.11 copy number variants (CNVs) have been associated with autism, schizophrenia, psychosis, intellectual disability, and epilepsy. The majority of 16p13.11 deletions or duplications occur within three well-defined intervals, and despite growing knowledge of the functions of individual genes within these intervals, the molecular mechanisms that underlie commonly observed clinical phenotypes remain largely unknown. Patient-derived, induced pluripotent stem cells (iPSCs) provide a platform for investigating the morphological, electrophysiological, and gene-expression changes that result from 16p13.11 CNVs in human-derived neurons. Patient derived iPSCs with varying sizes of 16p13.11 deletions and familial controls were differentiated into cortical neurons for phenotypic analysis. High-content imaging and morphological analysis of patient-derived neurons demonstrated an increase in neurite branching in patients compared with controls. Whole-transcriptome sequencing revealed expression level changes in neuron development and synaptic-related gene families, suggesting a defect in synapse formation. Subsequent quantification of synapse number demonstrated increased numbers of synapses on neurons derived from early-onset patients compared to controls. The identification of common phenotypes among neurons derived from patients with overlapping 16p13.11 deletions will further assist in ascertaining common pathways and targets that could be utilized for screening drug candidates. These studies can help to improve future treatment options and clinical outcomes for 16p13.11 deletion patients.